Beta diversity of macrophyte life forms: Responses to local, spatial, and land use variables in Amazon aquatic environments - Bomfim, Francieli F.; Carvalho, Lucimar S.; Sampaio, Fabiane B.; Juen, Leandro; Dias-Silva, Karina; Casatti, Lilian [UNESP]; Carmo, Rayssa S.; Sousa, Raimundo L.M.; Cabral, Guilherme S.; Costa, Antônio A.S.; Michelan, Thaisa S. (Elsevier, 2025)
Aquatic macrophytes encompass a highly diverse group of plants with different strategies, niche requirements, and dispersion capacities. Therefore, macrophyte life forms can respond distinctly to environmental factors. We analyzed whether emergent/amphibious, floating-leaves/rooted submerged, and free-floating/free-submerged macrophytes respond differently to local, spatial, and land use variables in ponds and streams of the Amazon. We sampled macrophytes and physical and chemical variables in 158 sites in the Pará state, Brazil. Land use and land cover were obtained via satellite images. A total of 264 macrophyte taxa were recorded, including 234 amphibious/emergent, 17 floating-leaves/rooted submerged, and 13 free-floating/free-submerged. The highest total beta diversity was recorded for amphibious/emergent species (0.47), followed by free-floating and floating submerged (0.41), and floating-leaves and rooted submerged species (0.39). The replacement component explained the greatest proportion of total beta for the three macrophyte groups, with values higher than 60 %. The spatial component greatly influenced the total beta diversity of amphibious/emergent (R2 = 0.06) and floating-leaves/rooted submerged life forms (R2 = 0.08). Meanwhile, local variables were more associated with the total beta diversity of free-floating/free-submerged macrophytes (R2 = 0.06). Free-floating and free-submerged life forms were the only groups influenced by land use changes (R2 = 0.02), and their richness difference between sites was spatially structured (R2 = 0.10). Our study is one of the first to explore the combined effects of local, spatial, and land use variables on macrophyte life forms. These results are important for deeply understanding macrophyte structure in Amazon environments, threatened by anthropic activities and planning conservation strategies.
Keywords: Anthropic actions; Aquatic plants; Landscape; Macrophyte functional groups; Metacommunity; Species' niche